التنبؤ المكاني بالخصائص الهيدروكيميائية للمياه الجوفية و تشخيص اثرها في صفات التربة باستخدام بعض الدلائل الطيفية /SpatialPrediction of Hydrochemical Properties of Groundwater and Diagnosis of Soil Characteristics Using some SpectralEvidence (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The study Carried out in the western part of Babylon Province , midst Iraq inside , located between  latitude 32º 04′27″.40 to32º41′09″.53 N and longitude 44º08′22″.35 to 44º 56′59″.58 E . This study is conducted to       Spatial predicted for Salinity, Sodium adsorption ratio and Groundwater suitable to irrigation by through the application of Spherical Model predicted an accurate 0.9993**, 0.9996** and 0.9944** each of  respectively, in addition to diagnosis of salinity, the Sodium Adsorption Ratio and Exchangeable Sodium Percentage   in the soil by Vegetation Indices using  Soil-Adjusted Vegetation Index, Optimized Soil-Adjusted Vegetation Index(OSAVI) and Generalized Difference Vegetation Index(GDVI2) an accurate 0.9919**, 0.9927** and 0.9878** each of  respectively . Furthermore the maps showed spatial fitting and highly significant correlation  between Salinity, Sodium Adsorption Ratio and Exchangeable Sodium percentage of soil with Salinity, Sodium Adsorption Ratio and Groundwater suitable to irrigation